2016
DOI: 10.1111/jfd.12452
|View full text |Cite
|
Sign up to set email alerts
|

Early‐stage sea lice recruits on Atlantic salmon are freshwater sensitive

Abstract: Sea lice are significant parasites of marine and brackish farmed fishes. Freshwater bathing is a potential control option against numerous sea lice species, although has been viewed as futile against those that are capable of tolerating freshwater for extended periods. By comparing freshwater survival times across host-attached stages of Lepeophtheirus salmonis (Krøyer), a key parasite in Atlantic salmon farming, we show the first attached (copepodid) stage undergoes 96-100% mortality after 1 h in freshwater, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…Because salmon lice do not tolerate low salinities for extended periods (Heuch, 1995;Wright, Oppedal, & Dempster, 2016), coastal migrating salmonids like sea trout (Salmo trutta L.) can actively reduce or get rid of a salmon lice infestation by seeking FW (Birkeland & Jakobsen, 1997;Gjelland et al, 2014;Wells et al, 2007). Nevertheless, spending time in the estuary or returning to a river has a cost of reduced foraging opportunity and efficiency (Birkeland, 1996).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Because salmon lice do not tolerate low salinities for extended periods (Heuch, 1995;Wright, Oppedal, & Dempster, 2016), coastal migrating salmonids like sea trout (Salmo trutta L.) can actively reduce or get rid of a salmon lice infestation by seeking FW (Birkeland & Jakobsen, 1997;Gjelland et al, 2014;Wells et al, 2007). Nevertheless, spending time in the estuary or returning to a river has a cost of reduced foraging opportunity and efficiency (Birkeland, 1996).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…To compute hourly distance from the individual fish to the river mouth, hourly mean positions of each fish were calculated using the weighted centre of activity (CA) method (Simpfendorfer, Heupel, & Hueter, 2002 Sea trout in or close to the river mouth may experience very low salinities and therefore high lice mortality, especially for newly infested lice (Birkeland & Jakobsen, 1997;Wright et al, 2016). Hence, we classified all hourly mean positions with distance <300 m from the middle of the river outlet ( Figure 1) as being in a delousing area, and the positions with distance ≥300 m from the river outlet as being in a marine area.…”
Section: Migratory Behaviour Of Tagged Fishmentioning
confidence: 99%
“…Even short-term exposure to reduced salinity levels severely compromises survival and host infectivity of salmon lice [22,23]. The fish in the present study had been too short time in the sea for development of adult salmon lice [41], but high levels of copepodids alone also caused premature freshwater return of sea trout [39].…”
Section: Discussionmentioning
confidence: 99%
“…The salinity history of the tagged fish indicated that the post-smolts occasionally spent time in sea water with lower salinity than 20.0 psu, especially in the inner part of the fjord. The utilization of salinities below 20.0 psu may reduce infestation risk by salmon lice [22,23], and the probability of infestation is generally shown to decrease with increasing freshwater influence [35]. Salmon louse is a marine parasite, which can severely reduce Atlantic salmon populations in farm-intensive areas [36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation